The Effect of KAP Reputation, Public Ownership, Audit Committee, Institutional Ownership, and Independent Commissioners on the Timeliness of Financial Report Submission - Arnindya, Fanisa Diva; Kusumawati, Eny (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study investigates the influence of audit firm reputation, public ownership, audit committee, institutional ownership, and independent commissioners on the timeliness of financial report submission in non-financial companies listed on the Indonesia Stock Exchange for the 2021–2023 period. Timeliness refers to the period between the fiscal year-end (December 31) and the submission date of audited reports to the Financial Services Authority (Bapepam-LK). Using purposive sampling, 738 firms were selected and analyzed with logistic regression, which passed model fit, feasibility, and coefficient of determination tests. Results show that only audit firm reputation significantly affects timeliness, suggesting that pressure from reputable external auditors plays a critical role in ensuring compliance. In contrast, the insignificance of internal governance mechanisms such as public ownership, audit committees, institutional ownership, and independent commissioners may reflect weak oversight functions or insufficient enforcement, possibly influenced by industry norms or firm-specific characteristics not captured in this model. The use of purposive sampling poses a limitation due to potential selection bias, which may affect the generalizability of the findings. Nonetheless, the study offers valuable insights for regulators, companies, and investors on the importance of audit quality in promoting timely financial disclosures and calls for further research into contextual and mediating variables affecting reporting behavior.